2015
DOI: 10.1016/j.bbi.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic gene expression changes in astrocytes in Multiple Sclerosis cerebral cortex are indicative of immune-mediated signaling

Abstract: Emerging as an important correlate of neurological dysfunction in Multiple Sclerosis (MS), extended focal and diffuse gray matter abnormalities have been found and linked to clinical manifestations such as seizures, fatigue and cognitive dysfunction. To investigate possible underlying mechanisms we analyzed the molecular alterations in histopathological normal appearing cortical gray matter (NAGM) in MS. By performing a differential gene expression analysis of NAGM of control and MS cases we identified reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 81 publications
2
49
0
Order By: Relevance
“…Although IL-1β and TNFα secreted from LPS-stimulated microglia have been reported to be the main factors that inhibit Cx43 expression and functions of GJs in astrocytes18, in our study, IL-1β alone decreased Cx43 protein levels and TNFα had no additional effect on the Cx43 protein reduction induced by IL-1β treatment. These data are in accordance with previous studies that reported IL-1β downregulates the expression of Cx43 in astrocyte-rich cultures2122. However, our present data differ from previous reports regarding the effects of proinflammatory cytokines on glial cells2324.…”
Section: Discussionsupporting
confidence: 88%
“…Although IL-1β and TNFα secreted from LPS-stimulated microglia have been reported to be the main factors that inhibit Cx43 expression and functions of GJs in astrocytes18, in our study, IL-1β alone decreased Cx43 protein levels and TNFα had no additional effect on the Cx43 protein reduction induced by IL-1β treatment. These data are in accordance with previous studies that reported IL-1β downregulates the expression of Cx43 in astrocyte-rich cultures2122. However, our present data differ from previous reports regarding the effects of proinflammatory cytokines on glial cells2324.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, the expression level of GLUT1 (SLC2A1), a major glucose transporter in the BBB, is down-regulated in brain lesions of MS patients [46]. Moreover, a recent 1 H-NMR study reported reduced levels of serum glucose in MS [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent report has elucidated that oligodendroglia metabolize glucose glycolytically to produce lactate . Glucose supplied from microvessels can be used as a direct substrate for oligodendroglia to support neuronal energy metabolism . The CMR glc in the white matter is much less than that in the gray matter, and the exact contributions of astroglia, oligodendroglia, and neurons (axons) to CMR glc and the pathways of glucose transport to oligodendroglia and neurons remain to be solved.…”
Section: Summary and Unsolved Issuesmentioning
confidence: 99%